Whitewashed : America's invisible Middle Eastern minority - Tehranian, John (Critical America., 2009)
Middle Easterners: Sometimes White, Sometimes Not - an article by John Tehranian. The Middle Eastern question lies at the heart of the most pressing issues of our time: the war in Iraq and on terrorism, the growing tension between preservation of our national security and protection of our civil rights, and the debate over immigration, assimilation, and our national identity. Yet paradoxically, little attention is focused on our domestic Middle Eastern population and its place in American society. Unlike many other racial minorities in our country, Middle Eastern Americans have faced rising, r.